Effect of orlistat on the total ghrelin and leptin levels in obese patients - Ozkan, Y.; Aydin, S.; Donder, E.; Koca, S. S.; Aydin, Suna; Ozkan, B.; Sahin, I. (Springer, 2009)
Y. OZKAN, S. AYDIN, E. DONDER, S.S. KOCA, S. AYDIN, B. OZKAN and SAHIN. Effect of orlistat on the total ghrelin and leptin levels in obese patients. J Physiol Biochem, 65 (3), 215-224, 2009. Obesity, characterized by hyperleptinemia and hypoghrelinemia, has become a major health problem all over the world and is associated with an increased risk of complications including insulin resistance, hypertension, dyslipidemia, diabetes mellitus and atherosclerosis. The use of the pancreatic lipase inhibitor Orlistat can help seriously overweight people to achieve and maintain weight loss. The aim of our study was to compare the serum leptin and ghrelin levels in obese subjects who take orlistat with those receiving only dietary treatment. Twenty-one obese patients and 10 control subjects participated. The obese patients were divided into two groups; one group (n=11) took orlistat (120 mg, 3 times daily) and received dietary treatment and the other (n=10) only received the dietary treatment. The study lasted twelve weeks. The concentrations of serum ghrelin, leptin, insulin and C-peptide, and routine biochemical parameters, were measured in both groups. The serum ghrelin level was higher in control (183 +/- 62 fmol/ml) than obese (59 +/- 30 fmol/ml) subjects while the plasma leptin level was lower in control (8.7 +/- 12 mu g/L) than obese (36.7 +/- 19 mu g/L) subjects (all p<0.001). BMI and the total blood cholesterol, LDL and triglyceride levels fell significantly after both orlistat and dietary treatment in the obese subjects (all p<0.01), and the plasma ghrelin level rose (p<0.01). The leptin level demonstrated the opposite trend in both groups but only the patients taking orlistat showed a significant change (p<0.05). Taken together, these results show that orlistat has no effect on body weight in obese subjects additional to that conferred by a non-pharmacological life-style intervention. We therefore conclude that weight lost rather than type of treatment might be more valuable in obesity.
Keywords: Obesity; Ghrelin; Leptin; Orlistat